Carbon dioxide assisted toluene side-chain alkylation with methanol over Cs-X zeolite catalyst. (July 2018) - Seo, Dong-Woo; Rahma, Sheikh Tareq; Reddy, Benjaram M.; Park, Sang-Eon
Graphical abstract: Highlights: Influence of CO2 during toluene side-chain alkylation with methanol was probed. Cs ion-exchanged and Cs2 O loaded zeolite X is a promising catalyst for alkylation. CO2 introduction increased yields of side-chain alkylation products. CO2 enhanced productivity by H2 removal through reverse water-gas shift reaction. Abstract: Zeolite Cs-X is an acknowledged representative basic catalyst useful for side-chain alkylation of toluene with methanol. In spite of numerous investigations, still there has been long lasting challenge for achieving high selectivity for side-chain alkylated products rather than ring alkylated products. In an effort to improve the yields of side-chain alkylated products, CO2 was introduced during the toluene side-chain alkylation with methanol at 425 °C over Cs loaded faujasite catalyst. The CO2 addition facilitated in removing the formed hydrogen by reverse water-gas shift reaction and enhanced the product yield. Interestingly, CO2 addition helped in obtaining higher yields of side-chain alkylation products including styrene/ethylbenzene and α-methylstyrene/iso-propylbenzene. The CO2 introduction resulted in less H2 formation in the product stream during the reaction. Mesoporosity was also introduced to the zeolite X to improve the activity and product selectivity.